Aspetti organizzativi e timing - De Biase, P.; Sani, G.; Biancalani, E.; Sangiovanni, M. (Lo Scalpello - Journal, 2019)
TIMING AND SETTING Open fractures are often caused by high-energy trauma and the trauma itself is a relevant problem in the approach to these fractures. Major trauma may lead to significant long-term morbidity and disability. The fracture itself may induce prolonged illness lasting up to 2 years after the event. Open fractures are defined as bone fractures associated with solution of continuity of the surrounding soft tissue, which puts into communication the external environment and the bone or haematoma derived from the fracture. This communication with the external environment may lead to higher infection rates, malunion and nonunion if not recognised and treated appropriately. Before 1850, most surgeons used to treat open fractures with early limb amputation, since sepsis and gangrene were common side-effects, which often lead to death. It was not until the early twentieth century that sterility techniques became widely accepted, in part thanks to the work of English surgeon Joseph Lister. Known as the father of sterile surgery, Lister was the first to recognise the importance of sterile techniques during surgery. This way, he managed to reduce mortality rates dramatically, from 25–50% to 9%. Today, more than a century later, although open fractures are no longer a cause of mortality, they are still the source of significant morbidity and disability following trauma.